2020
DOI: 10.1063/1.5120412
|View full text |Cite
|
Sign up to set email alerts
|

Coupled oscillators for computing: A review and perspective

Abstract: Coupled oscillators are highly complex dynamical systems, and it is an intriguing concept to use this oscillator dynamics for computation. The idea is not new, but is currently the subject to intense research as part of the quest for “beyond Moore” electronic devices. To a large extent, these efforts are motivated by biological observations: neural systems and mammalian brains, which seem to operate on oscillatory signals. In this paper, we give a survey of oscillator-based computing, with the goal of understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(134 citation statements)
references
References 126 publications
0
121
0
Order By: Relevance
“…A schematics of the network is shown in Fig. 1a Alternatively, the phases of an oscillator may serve as state variables, as described in 1,17,18 . Figure 1c shows one possible implementation.…”
Section: B Hopfield Network Hardwarementioning
confidence: 99%
See 1 more Smart Citation
“…A schematics of the network is shown in Fig. 1a Alternatively, the phases of an oscillator may serve as state variables, as described in 1,17,18 . Figure 1c shows one possible implementation.…”
Section: B Hopfield Network Hardwarementioning
confidence: 99%
“…Oscillator-based-computing (OBC) is a form of analog computing, where the phase and frequency of a periodic signal is used to carry and process information, and oscillator-oscillator interactions perform some form of collective computing 1 . OBC networks are now being explored for extremely challenging problems, such as NP-hard problems [2][3][4][5][6] or complex, super-efficient neural networks 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the SNNs as a signal morphological approach, another approach for brain-like computation is the collective-state computation that emulates brain-like computation at a high level ( Csaba and Porod 2020 ). This computational model originated from the Hopfield neural network ( Hopfield 1984 ), then extended to cellular neural networks ( Chua and Yang 1988 ), coupled oscillators ( Ignatov et al., 2017 ), and adiabatic annealing machines with probabilistic bits ( Borders et al., 2019 ) ( Figure 1 F).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such demonstrations include the D-Wave quantum annealer [13]- [15], optical parametric oscillator-based Coherent Ising machines (CIM) [16]- [18], and SRAM-based Ising machines that use CMOS annealing [19], as well as the new CMOS annealing processors that use processing-in-/near-memory [20]- [22]. Coupled oscillators have also been explored as an alternate non-Boolean approach to solving computationally hard problems [23]- [35], and more importantly, have recently been shown to behave as Ising machines [36]- [39] relevant to solving the Max-Cut problem. Wang et al [36], [37] and Chou et al [38] recently demonstrated Ising machines using resistively coupled sinusoidal oscillators operating under the influence of a second harmonic injection signal, and Dutta et al [39] showed a similar functionality in four capacitively coupled injection-locked VO2 oscillators.…”
Section: Introductionmentioning
confidence: 99%